Multi‐layered PCB distributed filter. Issue 3 (20th January 2021) - Bulja, S.; Kozlov, D.
Abstract: In this paper, multi‐layered print circuit board distributed resonators and filters are introduced. Here, the individual elements of the distributed resonator are made as part of a multi‐layered print circuit board, commonly used in the circuitry of transceiver boards. In this way, the unused real estate available on the board is used effectively. As a demonstrator of the proposed technology, a 2‐pole filter fabricated using a 5‐layer substrate and consisting of a matrix of 11 × 11 elements per resonator is fabricated and its performance is measured. Due to a large number of individual elements, which perform dimensional averaging of manufacturing inaccuracies, the filter obtained in this way not only requires no post‐production tuning, but it also has an extremely low profile of 5 o, which is the lowest profile to be reported in the literature. The filter was made to operate at a centre frequency of 1.8 GHz with an absolute bandwidth of 65 MHz. The measured and computed results are in good agreement.